Risk Factors Computer Vision Syndrome in Computer Engineering Students, Syiah University of Kuala - Fonna Indriyani; Saiful Basri; Cynthia Wahyu Asrizal (Publikasi Indonesia, 2022)
Computer Vision Syndrome (CVS) is a collection of symptoms related to computer use prolonged. This can occur from various factors consisting of individual factors, computer factors and environmental factors. Computer engineering students are a group of students who use computers in doing assignments and other activities in daily life. The purpose of this study was to determine the risk factors for CVS events in students of the Computer Engineering Study Program, Syiah Kuala University. This research is an observational analytic survey with a cross sectional. The sample used consisted of 164 students from the 2017-2019 class who were taken by the stratified random sampling method. Collecting data through self-assessment using a questionnaire. Statistical test using Chi square test for bivariate and to find out which risk factor is the most influential, multivariate analysis is used, namely logistic regression analysis. The results showed that 63.4% of Computer Engineering Students at Syiah Kuala University experienced CVS. The factors that were significantly associated with the incidence of CVS were gender (p=0.03), duration of computer use (p=0.01) and eye distance to the monitor (p=0.001).